2015
DOI: 10.1007/s12035-014-9052-7
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Administration During Early Postnatal Life Suppresses Hippocampal Neurogenesis

Abstract: Propofol is currently one of the most widely used intravenous anesthetics and has been indicated to induce cognitive dysfunction in adults. Here, we investigated the effects of propofol exposure during early postnatal life on hippocampal neurogenesis. Propofol (30 or 60 mg/kg) was administered to mice on either postnatal day (P) 7 or P7-P9; cell proliferation and neurogenesis in the dentate gyrus (DG) were evaluated on P8 or P17. It showed that exposure to propofol on P7 decreased hippocampal cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 43 publications
7
38
0
Order By: Relevance
“…Moreover, our results indicate that propofol-induced neuronal apoptosis could be the cause of neuronal deficit, and persistent neuronal apoptosis induced by multiple propofol exposures can lead to longlasting neuronal damage. In addition, propofol can also suppress neurogenesis in the developing brain (Erasso et al, 2013;Huang et al, 2016). Single propofol exposure may not suppress neurogenesis, or may only induce mild suppression of neurogenesis, so that neuronal density can recover rapidly in a compensatory mechanism; while multiple propofol exposures may induce severe suppression of neurogenesis, together with its more profound pro-apoptotic effect, ultimately result in persistent neuronal deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our results indicate that propofol-induced neuronal apoptosis could be the cause of neuronal deficit, and persistent neuronal apoptosis induced by multiple propofol exposures can lead to longlasting neuronal damage. In addition, propofol can also suppress neurogenesis in the developing brain (Erasso et al, 2013;Huang et al, 2016). Single propofol exposure may not suppress neurogenesis, or may only induce mild suppression of neurogenesis, so that neuronal density can recover rapidly in a compensatory mechanism; while multiple propofol exposures may induce severe suppression of neurogenesis, together with its more profound pro-apoptotic effect, ultimately result in persistent neuronal deficit.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanisms behind anesthetic-induced neurotoxicity and damage to the neuronal signaling pathways remain unclear. Nonetheless, apoptotic modulation is identified as the main mechanism of anesthetic-mediated cellular responses, which further correlates with the activation of many cellular signaling components such as cell death signals, cleavage of cytoskeletal proteins, signaling kinases, and DNA repair enzymes in neuronal as well as nonneuronal cells [3,[8][9][10]12,22,23]. In this study, the activation of caspase-3, ultrastructural changes in the brain, and TUNEL and NeuN staining reflected the impacts of propofol on the brains of neonatal mice, causing neurotoxicity at a critical developmental stage that led to longtern neurocognitive impacts on adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several anesthetics, including ketamine, midazolam, isoflurane, and propofol, have been reported to cause neurodegeneration in the developing brain and subsequent cognitive dysfunction in several animal models [2][3][4][5][6][7]10]. Propofol has also been reported to cause neuroapoptosis in the developing brain at clinically relevant concentrations and durations, leading to neurocognitive dysfunction [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrated that AKT pathway might be important for the spine development in early phase. Other study also indicated inactivation of AKT pathway after early postnatal application of propofol, which inhibited neurogenesis in dentate gyrus (DG) region (Huang et al, 2015). Neurotropic factor was also proposed to regulate spinogenesis (Cohen-Cory et al, 2010).…”
Section: 3mentioning
confidence: 97%